Psychological impact of the COVID-19 pandemic and suicide ideation in community adults in Portugal: preliminary data - Campos, Rui C.; Holden, Ronald R.; Pereira, Alexandra M. (Minerva Psychiatry, 2021)
BACKGROUND: The aim of the present study was to evaluate the perceived impact of the COVID-19 pandemic state of emergency in Portugal and the contribution of several socio-demographic and clinical variables, including having had a psychiatric diagnosis, on suicide ideation. Further, we tested whether the perceived impact of the pandemic mediated the association between having had a psychiatric diagnosis and suicide ideation. METHODS: A sample of 227 Portuguese community adults (183 women, 44 men) participated online. RESULTS: Low education, having had a psychiatric diagnosis, and the perceived psychological impact of the pandemic each related to the presence of suicide ideation. Perceived psychological impact partially mediated the association between having had a psychiatric diagnosis and suicide ideation, as indexed by the total score on the Suicide Ideation Scale. CONCLUSIONS: Individuals with a psychiatric diagnosis, with a lower education level, and with a perceived psychological impact of the pandemic are at greater risk for experiencing suicide ideation, and psychological impact appears to be stronger for persons with a psychiatric diagnosis and, thus, resulting in more suicide ideation. A potential limitation was the use of only three items for assessing the impact of the pandemic.